Pure economic loss in Malaysia's construction industry - Tee, Yeong Yih (2013)
Pure economic loss is financial loss unaccompanied by damage or injury other than the defective building itself. The position of pure economic loss in the United Kingdom as well as its commonwealth counterparts has gone through a complicated process but has finally taken up their stands. What about the position of this difficult and complex area in Malaysia? Most commentators, writers, lawyers and judges generally said that Malaysia allowes pure economic loss. They use the case of Dr Abdul Hamid Abdul Rashid & Anor v Jurusan Malaysia Consultant and Majlis Perbandaran Ampang Jaya v. Steven Phoa to support their contention. The subject of Dr Hamid?s case was the rear portion of plaintiff?s bungalow collapsed and the plaintiff sued inter alia, the engineer and contractor. The recent Steven Phoa?s case has formed a part of a series of interconnected cases dealing with the Highland Towers saga which flowed from a catastrophic collapse of tower blocks of apartments on a hillside in Kuala Lumpur. It is proposed that the judgments of the two cases are uncertain and unclear as to the existence of pure economic loss. The issue is whether the claims in these two cases come within the scope of pure economic loss. The objective of this study is therefore to reevaluate the application of principle of pure economic loss in Malaysia?s construction industry. This research is carried out by analyzing the relevant cases of pure economic loss in United Kingdom, Australia, Canada, Singapore and Malaysia. The findings of this project showed that Dr Hamid and Highland Tower cases was not a pure economic case but consequent economic case